'6 to 8 Slices Of Bread': Swedish health information campaigns in the 1970s. Issue 2 (15th March 2018) - Norén, Fredrik
Abstract : Swedish health information, conducted by the National Board of Health and Welfare in collaboration with private participants, expanded rapidly in the 1970s. This study examines a controversial bread campaign, which declared that the National Board, in collaboration with the private Bread Institute, wanted citizens to eat six to eight slices of bread every day. Why and how could such a seemingly unholy alliance come about? Contextualizing the collaborations with the industry, with a network governance approach, this article seeks the answers by investigating the organizational conditions behind the various campaigns. Different conflicting dilemmas influenced the campaigns and their outcomes. For example, the desire to maximize the disseminationof information, and at the same time controlling it, as well as the imbedded power dynamics between private and public sector. The result points to a shift from strong to weak interdependence between the government agency and collaborating parties, basically due to the agency's diminishing campaign resources, which opened up for a stronger commercialization of the bread campaign.